Vernacular Veiling: Rimpu, Embodied Piety, and Muslim Women's Agency in Bima - Arfaton; Rhoma Dwi Aria Yuliantri; Imran; Sitti Arafah (Balai Penelitian dan Pengembangan Agama Jakarta, 2026)
Studies of women’s Muslim attire often focus on standardised hijabs and the dichotomy of oppression versus resistance, resulting in vernacular practices and women’s agency being overlooked. Rimpu—the practice among women in Bima of wrapping the body in two traditional sarongs (Tembe nggoli)—is highlighted as a vernacular expression of religious identity. Drawing on ethnographic methods (interviews, observation, documentation) and Spradley’s analytical framework (domains, taxonomy, componential analysis, cultural themes), this study examines Rimpu through Saba Mahmood’s concept of ‘embodied piety’ and the field of veiled anthropology. The findings: Rimpu is more than just a set of functions; it is a vernacular representation of Islamic modesty standards. The Bima weaving tradition localises the global norm of body covering, resulting in a specific regional Muslim femininity as embodied piety. Rimpu is being supplanted by standardised global hijabs, which has prompted the revival of Rimpu as a cultural legacy through festivals and school curricula. Such revitalisation runs the risk of folklorizing a live practice while contributing to a theory of vernacular head-covering' that transcends the oppression-resistance duality by emphasising women's autonomy and the localisation of Islamic faith.